Test@work: evaluation of workplace HIV testing for construction workers using the RE-AIM framework - Wendy Jones; Sarah Somerset; Catrin Evans; Katharine Whittingham; Matthew Middleton; Holly Blake (BMC, 2021)
Abstract Background Community testing for HIV can reach previously untested populations but is rarely offered in workplaces. Targeting the construction sector could reach workers from high risk populations. Methods The RE-AIM framework was used to evaluate Test@Work, a workplace HIV testing intervention for construction workers implemented at 21 events (10 companies) in the UK. Test@Work had three components: 1) an online health toolkit to inform managers about health screening and HIV testing; 2) general health checks; and 3) opt-in HIV consultation and testing. Quantitative data were collected using registration and exit questionnaires with workers (n = 426) and pre/post-event questionnaires with managers (n = 15), with qualitative analysis of free text responses. Results Reach 426 individuals had health checks. Participants were broadly representative of the UK construction workforce, but with a higher proportion of permanent workers. Most workers reported being in good health but also believed their work had an adverse impact on their health. Effectiveness: 97% of health check participants opted to have a consultation about sexual health (n = 413) and 82% had an HIV test (n = 348), of whom 78% had not previously been tested. All HIV tests were non-reactive. HIV testing at work was considered acceptable by most participants. Participants reported learning new things about their health (74%), said they would make changes as a result (70%) and felt confident of success (median score 8/10). Adoption: Recruitment of companies was challenging and time consuming. Seven of the participating companies were very large, employing over 1000 workers, which is atypical of construction generally. Implementation: All events were completed as planned and were considered successful by all parties. Maintenance: All managers would arrange further events if they were offered them. Six managers incorporated sexual health awareness into their health programmes, but this was not possible for many as health agendas were set centrally by their organisations. Conclusions Opt-in HIV testing, when embedded within a general health check, has high uptake and acceptability in the UK construction sector, and reaches individuals at risk for HIV who may not otherwise attend for testing. Cost-effectiveness of this approach is yet to be determined. Trial registration ClinicalTrials.gov Identifier: NCT04292002 .